2020
DOI: 10.3389/fpsyg.2020.02255
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coronavirus Outbreak and Career Development: A Narrative Approach Into the Meaning for Italian University Graduates

Abstract: In times of economic crisis, the literature shows that young people have always been in the high-risk category. The COVID-19 outbreak and the consequence on the economic level have increased the sense of uncertainty and precariousness experienced by young people. The current scenario has forced young people at the school-to-work transition point to rethink their career plans. Although the difficulties of the school-to-work transition already lead to distress and mental health problems in young people, the slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 108 publications
3
35
0
5
Order By: Relevance
“…Recently, the potential negative impact that the adverse psychological consequences of COVID-19 further had on the disease itself have been highlighted in the literature (Center for Disease Control and Prevention, 2020;Lima et al, 2020;Parola, 2020;Parola et al, 2020;Thakur and Jain, 2020;Wind et al, 2020). Indeed, the advent of COVID-19 generated intense fear and anxiety about contagion, disease, and thoughts of death in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the potential negative impact that the adverse psychological consequences of COVID-19 further had on the disease itself have been highlighted in the literature (Center for Disease Control and Prevention, 2020;Lima et al, 2020;Parola, 2020;Parola et al, 2020;Thakur and Jain, 2020;Wind et al, 2020). Indeed, the advent of COVID-19 generated intense fear and anxiety about contagion, disease, and thoughts of death in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this study contributes to the current debate about the psychological implications of the COVID-19 pandemic, a prolonged and distressing situation triggering or worsening psychological issues. These findings may also be useful to help clinicians develop efficient and tailored interventions for increasing individuals' mental health -with particular attention to the more fragile categories, such as young people and elderly people (Parola andDonsì, 2018, 2019;Balestroni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting approach for future research is the use of thematic analysis (eg, narrative) to deepen the subjective meaning of the psychological experience of each patient. 54 Thus, regardless of different conditions and resources, the uniqueness of COVID-19 psychological impact should be highlighted in comparison to other epidemics and illnesses that did not reach these devastating consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The fear of COVID-19 and depression due to the pandemic have been explored in a growing number of studies that generally indicated high rates of prevalence and significant consequences on health literacy, health-related behaviors (Nguyen et al, 2020), delayed access, or provision of care (Lazzerini et al, 2020), and, eventually, on people's suicidal intentions and behaviors (Goyal et al, 2020). More importantly, fear of COVID-19 and depression of COVID-19 seem to have significant adverse consequences related to the forthcoming university graduates' future career anxiety, which now face higher rates of uncertainty related to the job market, career possibilities, and expectations (Mahmud et al, 2020;Parola, 2020). Building on several theories of emotion, Mahmud et al (2020) suggested that depression might be a consequence of the fear of Covid-19 experienced during the current pandemic and that, "due to the outbreak of COVID-19, the fear arises among the future workforce regarding their future career plan, which ultimately triggers career-related anxiety among them" (p.4).…”
mentioning
confidence: 99%